A new species of the armored spider genus Caraimatta Lehtinen, 1981 from Colombia (Araneae: Synspermiata: Tetrablemmidae) - García, Andrés F.; Martínez, Leonel; Ahumada-C, Daniela (Zootaxa, 2019)
A new species of the armored spider genus Caraimatta Lehtinen, 1981 from Colombian Tropical dry forest fragments is described and illustrated: Caraimatta brescoviti sp. nov. (based on male and female) from Bolivar and Sucre departments, representing the first record of the genus from Colombia. Additionally, photographs of Monoblemma muchmorei Shear, 1978 (other tetrablemmid species previously recorded from the country) are given. A map with the known distribution and an identification key for males and females of the Caraimatta species are also included.